Strengthening Micro, Small, and Medium Enterprises (MSMEs) Post COVID-19 Through Local Economic Development (LED) in Kampung Logam-Ngingas, Waru, Sidoarjo - Angelia Setya Lukita; Shoffan Maulana; Aflahah Ramadhani Nidia Saputri; Bintoro Wardiyanto; Bambang Suharto (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
This paper analyzes the impact of the Sidoarjo Governments in fostering Micro, Small, and Medium Enterprises (MSMEs) in Kampung Logam, Desa Ngingas, Waru, Sidoarjo using the Local Economic Development (LED) framework during the Covid-19 pandemic. Researchers discovered problems delegating tasks within the Department of Industry and Trade where overlapping functions across the industrial area, particularly Ngingas, impede MSME growth. Data were acquired through observations, document analysis, and in-depth interviews utilizing a descriptive qualitative methodology in Sidoarjo and Ngingas Village. Research demonstrates that although policies regarding privatization, demand generation, new firm formation, and transformation methods beneficially impact MSME growth, substantial enhancements in programming are required. This encompasses enhancing industrial technical services, fortifying workforce development, and establishing resilient long-term investment plans to guarantee sustainable growth for MSMEs.